Building Organizational Commitments Through Work Motivation, Work Environment and Job Satisfaction in Sweet Food SMIS in District: Membangun Komitmen Organisasional Melalui Motivasi Kerja, Lingkungan Kerja dan Kepuasan Kerja pada Makanan Ringan di Kecamatan - Ayu Lestari, Dwi Girl Nita Arkana; Abadiyah, Rifdah (Indonesian Journal of Law and Economics Review, 2022)
This study aims to examine more deeply the effect of work motivation, work environment and job satisfaction on job satisfaction in Snack Small Industries in Tarik District. In this study using quantitative methods. The total sample taken in this study amounted to 69 respondents at the IKM Snacks in Tarik District. Data collection techniques using questionnaires. Data analysis in this study includes validity test, reliability test, classical assumption test, multiple linear regression test, simultaneous test and partial test. The results of this study prove that work motivation, work environment and job satisfaction simultaneously have a significant effect on organizational commitment to the Snacks Small and Medium Enterprises in Tarik District. Work motivation partially has a significant effect on organizational commitment to Snack SMIs in Tarik District. The work environment partially has a significant effect on organizational commitment to SMI Snacks in Tarik District. Partial job satisfaction has a significant effect on organizational commitment to the Snack SMI in Tarik District.